2010
DOI: 10.1177/0265407509360902
|View full text |Cite
|
Sign up to set email alerts
|

Bound to interact: The divergent goals and complex interplay of attachment and sex within romantic relationships

Abstract: Attachment and sexual mating are distinct behavioral systems that serve different evolutionary functions. Although their behavioral manifestations may occur in isolation, romantic partners typically function simultaneously as sexual partners and as attachment figures. In recent years, researchers have focused their attention on the complex interplay between attachment processes and the sexual aspects of romantic love. In this manuscript, I review research that demonstrates the reciprocal relationship between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 33 publications
6
80
0
3
Order By: Relevance
“…This is consistent with previous research (e.g., Birnbaum, 2010;Brassard et al, 2012) linking insecure attachment with lower emotional and physiological sexual fulfillment. Attachment dynamics as described by Mikulincer, Shaver, & Pereg (2003;Fig.…”
Section: Most Noteworthy Among Our Results Is the Theme Of Differentisupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with previous research (e.g., Birnbaum, 2010;Brassard et al, 2012) linking insecure attachment with lower emotional and physiological sexual fulfillment. Attachment dynamics as described by Mikulincer, Shaver, & Pereg (2003;Fig.…”
Section: Most Noteworthy Among Our Results Is the Theme Of Differentisupporting
confidence: 93%
“…Both anxious and avoidant attachment patterns have been associated with lower rates of intimacy, arousal, and orgasms with a partner (in women; Birnbaum, 2008;Cohen & Veltsky, 2008). The extant research on attachment and sexuality suggests that attachment patterns manifest in sexual interactions similarly to other intimate ways of engaging (see Birnbaum, 2010, for a review). Similar to dyadic coping, sexual satisfaction in the context of a romantic relationship is an indicator for a complex interaction that occurs between two people.…”
Section: Sexual Satisfactionmentioning
confidence: 99%
“…For example, research has found that feelings of sexual closeness are an important contributor to couple satisfaction (Mirgain & Cordova, 2007;Patrick et al, 2007). Feelings of sexual closeness and intimacy have been found to contribute positively to relationship quality (Birnbaum, 2010;Davis, Shaver, & Vernon, 2004;Schachner & Shaver, 2004). In a study that asked participants to rate concepts they saw as central to sexual intimacy, most associated sexual intimacy with feeling passionate, attraction, consensual, sexual contact, and closeness.…”
Section: Extending Closeness Discrepancy Theory To the Sexual Domainmentioning
confidence: 99%
“…On the other hand, the sexual behavior and motives of highly anxious people tend to be complicated. They often use sex as a tool to influence their partners' emotions and behavior, especially when they feel that their relationships are threatened (Birnbaum 2010). Importantly for the current study, anxiously attached people tend to disapprove of sex outside of a committed relationship (Brassard et al 2007).…”
Section: Adult Attachmentmentioning
confidence: 71%
“…Highly avoidant people tend to either completely disregard sexual activity or to engage in it purely for physical pleasure rather than emotional intimacy (Brassard et al 2007). Even in a monogamous relationship, highly avoidant individuals tend to not be as affected by problems in their sex lives; they may simply disengage (Birnbaum 2010). On the other hand, the sexual behavior and motives of highly anxious people tend to be complicated.…”
Section: Adult Attachmentmentioning
confidence: 99%